Management : A Global Perspective - Weihrich, Heinz and Koontz, Harold (New York McGraw-Hill, 1994)
This tenth edition of a classic management textbook features a new emphasis on global management. Equal attention is paid to the new Europe and the Pacific Rim as to the United States, and chapter cases are both domestic and international.
Include Glossary and Index
Keywords: Management -- Industrial management